2019
DOI: 10.1038/s41598-019-49352-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the VDW interaction converting DMAPS from the thermal-motion form to the hydrogen-bonded form

Abstract: Assessment of van der Waals (VDW) interactions is fundamental to all of the central quest of structure that regulates the biological function. VDW interactions contributing to intramolecular weak hydrogen bonding are regarded as an important force to regulate the thermal stimuli-sensitive function of sulfobetaine methacrylate, DMAPS. We present here the conversion from the thermal-motion form at room temperature to the weak-hydrogen-bonded form against thermal motion as a terahertz spectral change with a defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 55 publications
4
19
1
Order By: Relevance
“…Some CPPs use lipid rafts for nonendocytic cellular uptake. , Moreover, the translocation mechanisms depend on the differences in the molecular structures of the four polysulfobetaines (Scheme ). Simple aliphatic P­(DMAPS) aggregates are formed by dipole–dipole and hydrophobic interactions between the intra/inter-polymer chains . Hydrophobic association with the lipid bilayer core is attributed to the inner salt formation of the sulfobetaine moiety in P­(DMAPS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some CPPs use lipid rafts for nonendocytic cellular uptake. , Moreover, the translocation mechanisms depend on the differences in the molecular structures of the four polysulfobetaines (Scheme ). Simple aliphatic P­(DMAPS) aggregates are formed by dipole–dipole and hydrophobic interactions between the intra/inter-polymer chains . Hydrophobic association with the lipid bilayer core is attributed to the inner salt formation of the sulfobetaine moiety in P­(DMAPS).…”
Section: Resultsmentioning
confidence: 99%
“…Simple aliphatic P-(DMAPS) aggregates are formed by dipole−dipole and hydrophobic interactions between the intra/inter-polymer chains. 48 Hydrophobic association with the lipid bilayer core is attributed to the inner salt formation of the sulfobetaine moiety in P(DMAPS). P(ePySMAAm) and P(mPySMAAm) have π−π, NH−π, and cation−π interactions between the pyridyl sulfobetaine and methacrylamide chains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…29 From the viewpoint of an implicit approach such as the PCM, these corrections are based on free-particle interactions disregarding the presence of the environment. While appropriate in case that both interacting particles are within the same cavity, 30 this approach disregards screening by an implicit environment. It was therefore suggested to scale the van der Waals contributions by ε −2 (ω) with ω in an optical range.…”
Section: The Journal Of Chemical Physicsmentioning
confidence: 99%
“…We reveal the local environment of hydrated ions in the crystal from the temperature-dependent behavior of weak hydrogen bonds connected to hydration water and two chloride ions under the hydrogen-bonded network. In our previous study, we found, using synchrotron Fourier transform infrared (FTIR) microspectroscopy and THz spectroscopy, that a remarkable temperature-dependent spectral change occurs around 300 cm – 1 and is related to the thermal cleavage of weak hydrogen bonds at the van der Waals limit . Since the previous study was an amorphous system, the molecular conformation was unknown and deduced from the matching of calculated and observed spectral patterns.…”
Section: Introductionmentioning
confidence: 99%